基于虚拟样机的回转平台传动系统动力学与控制方法研究 - 方子帆; 周刚; 吴德新; 肖华攀; 何孔德; 杨蔚华 (Jixie chuandong)
A rotary platform is studied.The control method of its electromechanical transmission system is studied by usingvirtual prototype technology and control theory.Virtual prototype model of rotary platformis established in RecurDyn/Gear based on the Hertz elastic contact theory.A feed-forward link and three-ring control systemwhich are position,speed and current control link are designed in Colink.And then,the mechanical and control simulation model is setup.The response of the typical position command signal is analyzed.The simulation results show that the control method has effective engineering application,and the method can satisfy the objective of engineering control and a reference for the design and analysis of other electromechanical transmission control system is provided.